2016
DOI: 10.1113/jp273012
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic modulation of the parafacial respiratory group

Abstract: Active inspiration and expiration are opposing respiratory phases generated by two separate oscillators in the brainstem: inspiration driven by a neuronal network located in the preBötzinger complex (preBötC) and expiration driven by a neuronal network located in the parafacial respiratory group (pFRG). While continuous activity of the preBötC is necessary for maintaining ventilation, the pFRG behaves as a conditional expiratory oscillator, being silent in resting conditions and becoming rhythmically active in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 45 publications
13
51
0
Order By: Relevance
“…) and cholinergic (Boutin et al . ) neurotransmission in the RTN/pFRG have now been reported to induce active expiration in anaesthetized rats. Disinhibition of these neurons has been shown to underlie the recruitment of active expiration (Pagliardini et al .…”
Section: Discussionmentioning
confidence: 96%
“…) and cholinergic (Boutin et al . ) neurotransmission in the RTN/pFRG have now been reported to induce active expiration in anaesthetized rats. Disinhibition of these neurons has been shown to underlie the recruitment of active expiration (Pagliardini et al .…”
Section: Discussionmentioning
confidence: 96%
“…V T was obtained by integration of the airflow recording and converted to millilitres of air using a five‐point calibration curve (range 0.5–5 ml) (Boutin et al . ). Parameters during drug application were compared with the average value during a 2 min control period preceding drug application.…”
Section: Methodsmentioning
confidence: 97%
“…In more detail, expiratory muscle activation is caused by neurons of this area under hypercapnic conditions (Janczewski and Feldman 2006;Smith et al, 2007;Abdala et al, 2009;Pagliardini et al, 2011) or following peripheral chemoreceptor stimulation (Moraes et al, 2012). Furthermore, serotoninergic or cholinergic muscarinic mechanisms contribute to the appearance of neuronal expiratory activity within the RTN/pFRG region and promote the recruitment of expiratory motoneurons and active expiration (Lemes et al, 2016;Boutin et al, 2017). Neuronal recordings within this structure (Sugiyama et al, 2015) showed that the majority of recorded neurons changed activity in synchrony with coughing and swallowing.…”
Section: Neuronal Recordings C-fos Immunohistochemistry and Lesion Ementioning
confidence: 99%